2008
DOI: 10.1111/j.1574-6968.2007.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial endophytes: recent developments and applications

Abstract: Endophytic bacteria have been found in virtually every plant studied, where they colonize the internal tissues of their host plant and can form a range of different relationships including symbiotic, mutualistic, commensalistic and trophobiotic. Most endophytes appear to originate from the rhizosphere or phyllosphere; however, some may be transmitted through the seed. Endophytic bacteria can promote plant growth and yield and can act as biocontrol agents. Endophytes can also be beneficial to their host by prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
743
0
75

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,280 publications
(823 citation statements)
references
References 72 publications
5
743
0
75
Order By: Relevance
“…recovered from plant tissues seems to be a promising source of natural bioactive compounds in addition to soil-borne streptomycetes (Zin et al 2007). It is well accepted that control of phytopathogens through production of some useful compounds is one of the contributions made by any given endophyte to the host-endophyte relationship Ryan et al 2008). Indeed, numerous reports have shown that endophytic actinobacteria can have the capacity to control plant pathogens, although most of the conclusions were reached only doing in vitro assays (Cao et al 2004;Schulz 2006;Tan et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…recovered from plant tissues seems to be a promising source of natural bioactive compounds in addition to soil-borne streptomycetes (Zin et al 2007). It is well accepted that control of phytopathogens through production of some useful compounds is one of the contributions made by any given endophyte to the host-endophyte relationship Ryan et al 2008). Indeed, numerous reports have shown that endophytic actinobacteria can have the capacity to control plant pathogens, although most of the conclusions were reached only doing in vitro assays (Cao et al 2004;Schulz 2006;Tan et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ryan et al (2008) confirmaram que essas bactérias têm potencial para retirar contaminantes do solo, aumentando a fitorremediação, além de contribuir para a fertilidade do solo por meio da solubilização de fosfato e fixação de nitrogênio.…”
Section: Introductionunclassified
“…Endophytic bacteria seem to be distributed in most plant species and have been isolated from roots, leaves, and stems, and a few from flowers, fruits, and seeds (Lodewyckx et al 2002). Endophytic bacteria may accompaniment certain metabolic properties, such as promoting plant growth, controlling soil-borne pathogens, or helping host plant to defeat stress responses to environmental abuse (Mastretta et al 2006;Taghavi et al 2007;Ryan et al 2008). Furthermore, the interactions between plants and bacteria help plants to settle in ecosystem restoration processes (Glick et al 1995).…”
Section: Introductionmentioning
confidence: 99%